ANALISIS PENGARUH SOCIAL ENGINEERING TERHADAP KEBOCORAN DATA PENGGUNA MEDIA SOSIAL DITINJAU DARI UNDANG-UNDANG TENTANG PELINDUNGAN DATA PRIBADI - Diana Darmayanti Putong; Courtney Tuilan; Gyan Imanuel Mowoka; Sisilia Keloay; Gilbert Katang; Olivia Karundeng; Gusti Randa Sarigin (Jurnal Hukum to-ra : Hukum untuk mengatur dan melindungi masyarakat, 2026)
This study aims to analyze the extent to which social engineering influences data leaks among social media users in Indonesia and to identify the factors that increase their vulnerability. A quantitative approach was used in this study by distributing an online questionnaire to 325 respondents who are active social media users from various backgrounds. Regression analysis shows that exposure to social engineering, particularly phishing and impersonation techniques, has a significant influence on the likelihood of data leaks. In addition, the level of information security awareness was found to moderate this relationship. This study concludes that personal data leaks are not only caused by technical weaknesses, but also by human factors that can be manipulated psychologically. The implications of this study suggest the need to improve digital security literacy, provide advanced security features on social media platforms, and strengthen personal data protection regulations in Indonesia.